Relationship Between Stressful Life Events And Depression - Subedi, A; Khattri, JB; Tirkey, S; Lamichhane, RP (Journal of Psychiatrists' Association of Nepal, 2020)
Introduction: Stressful life events are associated with mental health breakdown. Many researches had shown that depression was preceded by stressful life events. The objective of this study was to measure the prevalence of significant score of stress scale in patients diagnosed as depressive episode. The next objective was to find out the association between the different sociodemographic variables and stress score and whether age is the predictor of stress score or not. Material And Method: The patients diagnosed as depressive episodes were selected from the out-patient unit of Department of Psychiatry of Manipal Teaching Hospital, Pokhara, Nepal. The proforma was used to collect the sociodemographic profile of the patient and Holmes and Rahe’s stress scale was applied. The diagnosis of depressive episode was made according to the International Classification of Disease-10 Classification of Mental and Behavioural Disorders: Diagnostic Criteria for Research. The stress score more than 150 was considered as significant stress score in this study. Results: The prevalence of significant stressful life events was 42%. The sociodemographic variables found that prevalence of stressful life events was found higher in female gender, illiterate individual, married and business/employed individual. The age of the patient was not the predictors of stress score in this study. Conclusion: These findings help us to understand that stressful life events were associated with depression. Effective coping skills and psychological interventions will improve quality of life in stressed individual.